Tumor-Targeted Erythrocyte Membrane Nanoparticles for Theranostics of Triple-Negative Breast Cancer - Moon Jung Choi; Yeon Kyung Lee; Kang Chan Choi; Do Hyun Lee; Hwa Yeon Jeong; Seong Jae Kang; Min Woo Kim; Young Myoung You; Chan Su Im; Tae Sup Lee; Yong Serk Park (MDPI AG, 2023)
Triple-negative breast cancer (TNBC) cells do not contain various receptors for targeted treatment, a reason behind the poor prognosis of this disease. In this study, biocompatible theranostic erythrocyte-derived nanoparticles (EDNs) were developed and evaluated for effective early diagnosis and treatment of TNBC. The anti-cancer drug, doxorubicin (DOX), was encapsulated into the EDNs and diagnostic quantum dots (QDs) were incorporated into the lipid bilayers of EDNs for tumor bio-imaging. Then, anti-epidermal growth factor receptor (EGFR) antibody molecules were conjugated to the surface of EDNs for TNBC targeting (iEDNs). According to the confocal microscopic analyses and biodistribution assay, iEDNs showed a higher accumulation in EGFR-positive MDA-MB-231 cancers in vitro as well as in vivo, compared to untargeted EDNs. iEDNs containing doxorubicin (iEDNs-DOX) showed a stronger inhibition of target tumor growth than untargeted ones. The resulting anti-EGFR iEDNs exhibited strong biocompatibility, prolonged blood circulation, and efficient targeting of TNBC in mice. Therefore, iEDNs may be used as potential TNBC-targeted co-delivery systems for therapeutics and diagnostics.